The Kindle : pricing complementary products in a competitive market - Oster, Sharon M.; Belford, Kristine; Janik, Arthur; Smith, Andrea Nagy ([London] : SAGE, 2016)
The Kindle, a portable electronic reading device sold by online retailer Amazon.com, is changing the experience of reading. This study examines the impact of the Kindle on the book business as a whole.
Originally Published in: Oster, S., Belford, K., Janik, A., & Nagy Smith, A. (2009). The Kindle: Pricing Complementary Products in a Competitive Market. 09-027. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Amazon.com (Firm); Kindle (Electronic book reader); Pricing -- Case studies; Competition -- Case studies